Flame-retardant fabric with infrared shielding performance and preparation method thereof

By using magnesium hydroxide/zinc oxide composite filler and surface-modified polyimide composite fibers in fabrics, the problems of degraded infrared shielding efficiency and insufficient flame retardant performance in existing fabrics under high temperature environments are solved, and the overall fabric is achieved Improved performance and suitable for high-strength protection.

CN119194709AActive Publication Date: 2024-12-27HEFEI AIJIA RADIATION PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411718356.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-27
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Existing infrared shielding and flame retardant fabrics show the problem of reduced infrared shielding efficiency and insufficient flame retardant performance in high temperature or strong radiation environments, mainly due to insufficient synergistic effects between infrared shielding components and flame retardant components, dispersion and The interface bonding force is weak.

Method used

Magnesium hydroxide/zinc oxide composite filler and surface-modified polyimide composite fiber are used to load on zinc oxide particles through magnesium hydroxide nanowires, combining dopamine-modified graphene, polyethylene glycol and alkaline zinc carbonate. Design the component proportions and textile density of the yarn to enhance the infrared shielding, flame retardant and mechanical properties of the fabric.

Benefits of technology

It significantly improves the infrared shielding, flame retardant and mechanical properties of the fabric, ensures stable performance under high temperature environments, extends service life, and expands its application potential in the field of multifunctional protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194709A_ABST
    Figure CN119194709A_ABST
Patent Text Reader

Abstract

The invention relates to the field of functional fabrics, and provides a flame-retardant fabric with infrared shielding performance and a preparation method thereof, and the fabric is prepared from blended yarns of polyester composite fibers and surface modified polyimide composite fibers through a textile process. The polyester composite fiber comprises magnesium hydroxide / zinc oxide composite filler and is prepared through melt blending and spinning, and the surface modified polyimide composite fiber is obtained through basic zinc carbonate surface modification treatment. Zinc oxide particles and magnesium hydroxide nanowires in the magnesium hydroxide / zinc oxide composite filler have a synergistic effect, so that the flame retardance and the infrared shielding capability of the fiber are enhanced; the use of the surface modified graphene improves the mechanical and thermal stability of the polyimide fiber. By reasonably regulating and controlling the fiber proportion and weaving density, the fabric has excellent mechanical property, infrared shielding property and flame retardant property while ensuring the flexibility, and has wide application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of functional fabrics, and in particular to a flame-retardant fabric with infrared shielding performance and a preparation method thereof. Background Art

[0002] In high-temperature or high-radiation environments, the protective properties of materials are crucial. This is particularly true in the military, aerospace, and construction sectors, where infrared shielding and flame retardancy are key requirements for fabrics. These applications often involve complex environments such as extreme temperatures, intense infrared radiation, and fire. Therefore, materials must not only effectively block infrared radiation to prevent detection and overheating, but also exhibit excellent flame retardancy to mitigate potential fire hazards. These fabrics must maintain structural strength and flexibility while exhibiting high thermal stability, oxidation resistance, and excellent aging resistance to ensure a long service life and maintain stable performance in harsh environments. Infrared shielding not only helps these fabrics achieve more effective stealth in applications such as military camouflage and energy management, but also reduces surface temperatures by reflecting and scattering radiant heat, extending their service life. Flame retardancy, on the other hand, effectively reduces the burning rate and release of harmful gases during a fire, enhancing the material's safety. Therefore, developing a fabric material with both infrared shielding and flame retardancy would not only significantly enhance its protective performance in high-temperature, high-radiation environments, but also broaden its application in industrial and firefighting fields, promoting the development of related industries.

[0003] At present, although the existing technology has made certain progress in the research and development of infrared shielding and flame-retardant fabrics, there are still obvious shortcomings. For example, Chinese patent publication number CN118048784A discloses a flame-retardant functional layer on the surface of a fabric, its preparation method, and flame-retardant fabric. Although it has basic flame-retardant functions, its infrared shielding efficiency still has a lot of room for improvement in high temperature or strong radiation environments. In particular, under long-term exposure to high radiation, the infrared heat reflectivity of the material gradually decreases, affecting its stealth effect. In addition, in terms of flame retardant performance, the flame retardant efficiency of existing materials in high temperature environments is limited, and the thermal decomposition products of the materials easily lead to intensified combustion, making the flame retardant effect difficult to sustain. The main reason for these problems is the lack of synergy between the materials, especially the weak dispersibility and interfacial bonding between the infrared shielding component and the flame retardant component, which makes it impossible to stably exert their respective properties in high temperature environments. Existing composite material designs often focus on improving a single performance while ignoring the importance of multifunctional synergistic effects. Therefore, how to achieve synergistic improvement of infrared shielding and flame retardant properties through surface modification and structural optimization of materials remains a key challenge in current research. Summary of the Invention

[0004] (1) Technical problems solved The purpose of the present invention is to provide a flame-retardant fabric with infrared shielding performance and a preparation method thereof, so as to solve the problem that the current fabrics are insufficient in infrared shielding and flame-retardant performance.

[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: A flame-retardant fabric with infrared shielding properties, obtained by weaving yarns as warp and weft respectively, wherein the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers; The polyester composite fiber is prepared by the following components in parts by mass: 4.0 to 8.0 parts of magnesium hydroxide / zinc oxide composite filler, 50 to 90 parts of polyester chips, 0.5 to 2.5 parts of polyethylene glycol and 0.4 to 1.2 parts of phthalate; The magnesium hydroxide / zinc oxide composite filler is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly loaded on the surface of the zinc oxide particles; The surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate; The polyimide composite fiber is prepared by the following components in parts by mass: 0.5~3.5 parts of surface-modified graphene, 1.5~4.0 parts of polyethylene glycol, 40~60 parts of 4,4'-diaminodiphenyl ether, 36~54 parts of pyromellitic dianhydride, and 100~250 parts of N,N-dimethylformamide; The surface-modified graphene is obtained by surface-modifying graphene oxide with dopamine.

[0006] Furthermore, the preparation method of the magnesium hydroxide / zinc oxide composite filler is as follows: in parts by weight, 20 to 45 parts of zinc oxide particles, 3.5 to 8.0 parts of magnesium chloride, 1.5 to 3.5 parts of magnesium oxide and 50 parts of deionized water are mixed evenly and added to a Teflon-lined high-pressure reactor, and kept warm at 150 to 170° C. for 6 to 10 hours. After the reaction is completed, the white precipitate is filtered and collected, and then the white precipitate is washed with deionized water 3 times. Then, the washed white precipitate, 3.0 to 6.0 parts of sodium hydroxide and 80 parts of anhydrous ethanol are added to a stainless steel autoclave, and kept warm at 110 to 130° C. for 5 to 9 hours. The solid powder is collected after filtration, and then washed with deionized water 3 times. Finally, it is dried in a vacuum drying oven at room temperature to constant weight to obtain a magnesium hydroxide / zinc oxide composite filler.

[0007] Furthermore, the mass ratio of the magnesium hydroxide to the zinc oxide is (5-15):(95-85).

[0008] Furthermore, the average diameter of the magnesium hydroxide nanowires is 35-70 nm, the average length is 100-350 nm, and the average particle size of the zinc oxide particles is 400-2000 nm.

[0009] Furthermore, the preparation method of the polyester composite fiber is as follows: magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol and phthalate are mixed evenly, added into a twin-screw extruder, melt blended, then extruded, and fibers are sprayed out through a spinneret, and the polyester composite fiber is obtained after cooling.

[0010] Furthermore, the screw aspect ratio of the twin-screw extruder is (25-40):1.

[0011] Furthermore, the extrusion temperature of the twin-screw extruder is 240-280°C.

[0012] The magnesium hydroxide / zinc oxide composite filler of the present invention is designed to improve the infrared shielding capability, flame retardancy, and mechanical properties of fabrics. The magnesium hydroxide / zinc oxide composite filler employed in the present invention is primarily designed to enhance the infrared shielding capability, flame retardancy, and mechanical properties of fabrics. By uniformly loading magnesium hydroxide nanowires onto the surface of zinc oxide particles, this composite filler exhibits excellent synergy within the material, effectively improving the overall performance of the fabric. Magnesium hydroxide, a common inorganic flame retardant, possesses excellent thermal stability and flame retardancy. Its nanowire structure not only enhances its dispersibility within the matrix but also further enhances the material's flame retardancy through the nanoscale effect. Zinc oxide particles not only possess excellent thermal conductivity and optical properties, but their reflective and scattering capabilities within the infrared spectrum also enable the composite material to effectively shield infrared radiation, thereby enhancing the fabric's infrared shielding performance. Furthermore, the synergistic effect of magnesium hydroxide and zinc oxide at high temperatures enhances the composite's thermal protection. Magnesium hydroxide decomposes at high temperatures to produce water vapor and hydroxides, a process that absorbs significant heat, slowing the temperature rise of the material. Simultaneously, the generated water vapor dilutes surrounding combustible gases, thereby enhancing the material's flame retardancy. Zinc oxide particles exist stably at high temperatures, further enhancing the material's resistance to thermal shock. The combination of the two enables the material to exhibit stronger thermal protection capabilities in high-temperature scenarios such as fire. In terms of mechanical properties, the introduction of magnesium hydroxide nanowires not only improves the strength and rigidity of the material, but its high aspect ratio structure can also enhance the material's tensile strength through the filling effect of multi-dimensional space. At the same time, the large specific surface area of ​​zinc oxide particles forms a strong interfacial bonding force with the polymer matrix. This interfacial effect helps to improve the mechanical properties of the composite material. The synergistic effect of the two enables the fabric to have higher mechanical strength while maintaining flexibility, adapting to more stringent application scenarios. In short, the present invention effectively combines the advantages of the two in infrared shielding, flame retardancy and mechanical properties through the design of magnesium hydroxide / zinc oxide composite fillers, giving the fabric excellent comprehensive performance, and through reasonable component proportions and preparation processes, ensuring the synergy between the components, significantly improving the application potential of the fabric in the field of multifunctional protection.

[0013] Furthermore, the preparation method of the surface-modified polyimide composite fiber is as follows: after uniformly mixing 2.5 to 5.5 parts of basic zinc carbonate and 100 parts of 5 wt.% sodium hydroxide solution by weight, the polyimide composite fiber is completely immersed in the mixed solution, the immersion time is 30 to 60 minutes, the immersion temperature is 60 to 80°C, and after the immersion is completed, it is washed with deionized water 3 times, and finally dried at room temperature to completely obtain the surface-modified polyimide composite fiber.

[0014] Furthermore, the preparation method of the polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and ultrasonicated for 30 to 45 minutes to obtain a uniformly dispersed suspension, and then the suspension is added to a reactor, and under a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and pyromellitic dianhydride are continued to be added, and the polycondensation reaction is carried out with stirring at 5 to 25 ° C. The reaction time is 10 to 15 hours. After the reaction is completed, a polyamic acid mixed solution is obtained, and after standing and vacuum degassing treatment, solution spinning is carried out to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are subjected to thermal imidization and heat setting stretching treatment at 300 to 550 ° C. The treatment time is 30 to 60 minutes, and the polyimide composite fiber is obtained after cooling.

[0015] Furthermore, the preparation method of the surface-modified graphene is as follows: 0.5 to 2.5 parts of graphene oxide are added to 100 parts of deionized water in parts by weight, and after stirring evenly, 0.05 to 0.09 parts of dopamine are added, and then the pH is adjusted to 8.0 to 10.0 with ammonia water, and the reaction is continuously stirred at room temperature for 6 to 12 hours. After stirring is completed, the mixed solution is centrifuged to collect the solid precipitate, and then the precipitate is washed once with deionized water, and finally dried to constant weight in a vacuum drying oven at room temperature to obtain surface-modified graphene.

[0016] Furthermore, the mass ratio of the 4,4'-diaminodiphenyl ether to pyromellitic dianhydride is 1:0.9.

[0017] The surface-modified polyimide composite fiber designed by the present invention has the following multiple purposes: through the synergistic effect of dopamine surface-modified graphene, polyethylene glycol and basic zinc carbonate, the flame retardant, infrared shielding and thermal management properties of the fiber are significantly improved. First, dopamine surface-modified graphene plays a key role in the composite material. After being modified with dopamine, graphene oxide not only retains the excellent conductivity of its two-dimensional lamellar structure, but also forms a surface coating with better compatibility with the matrix through the self-polymerization of dopamine. This modification process improves the dispersibility of graphene in the polyimide matrix, allowing it to be more evenly distributed in the fiber, thereby significantly enhancing the infrared shielding effect of the material. Dopamine surface-modified graphene also has excellent flame retardant properties and can form a stable carbonized layer when subjected to high temperature, thereby blocking heat transfer and reducing the burning rate of the material. Polyethylene glycol has a dual function in this composite fiber system. First, polyethylene glycol, as a good dispersant, effectively improves the dispersion of surface-modified graphene within the composite fiber, further enhancing the uniformity and overall performance of the composite. Second, polyethylene glycol exhibits phase-change endothermic properties. When the ambient temperature rises, it absorbs significant amounts of heat energy to mitigate the temperature rise of the fiber, thereby improving the thermal management capabilities of the composite. The addition of this phase-change material not only enhances the thermal stability of the fiber but also provides it with temperature control capabilities, enabling it to maintain stable performance in overheated environments. The introduction of basic zinc carbonate further enhances the material's flame retardancy and infrared shielding properties. Under high temperature conditions, basic zinc carbonate first undergoes thermal decomposition, releasing flame-retardant gases that form a physical barrier, reducing oxygen infiltration and heat transfer, thereby effectively suppressing combustion. Its thermal decomposition product, zinc oxide, exhibits excellent infrared shielding capabilities within the composite fiber, effectively reflecting and scattering infrared radiation, enhancing the material's infrared stealth properties. Furthermore, the presence of zinc oxide further improves the fiber's thermal stability, resulting in improved heat resistance and mechanical strength in high-temperature environments. In summary, the surface-modified polyimide composite fiber of the present invention successfully achieves multiple functions of flame retardancy, infrared shielding, and thermal management through the synergistic effects of dopamine-surface-modified graphene, polyethylene glycol, and basic zinc carbonate. These components work together to enhance the overall performance of the material while also ensuring excellent stability and safety in high-temperature environments, promising broad application prospects.

[0018] Furthermore, the average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber are 8-15 μm and 6-12 μm, respectively.

[0019] Furthermore, the mass ratio of the polyimide composite fiber to the surface-modified polyimide composite fiber in the yarn is (30~50):(70~50).

[0020] Furthermore, the warp yarn weaving density of the yarn is 30-60 yarns / cm, and the weft yarn weaving density is 25-50 yarns / cm.

[0021] The present invention utilizes polyimide composite fibers and surface-modified polyimide composite fibers primarily to enhance the mechanical properties, infrared shielding properties, and flame retardancy of the yarn. By rationally controlling the fiber diameters and the mass ratios of the various components in the yarn, the present invention effectively improves multiple performance characteristics. First, the average diameters of the polyimide composite fibers and surface-modified polyimide composite fibers are 8-15 μm and 6-12 μm, respectively. The smaller diameter of the surface-modified fibers not only enhances the fiber's flexibility and mechanical strength but also improves the uniformity of fiber distribution within the yarn. This design helps improve the yarn's overall structural stability, resulting in better processing and mechanical performance during the weaving process. Second, the mass ratio of the polyimide composite fibers to the surface-modified polyimide composite fibers in the yarn is designed to be (30-50):(70-50), a ratio that fully considers the complementary properties of the two fibers. The polyimide composite fibers themselves possess excellent thermal stability and flame retardancy, while the surface treatment of the surface-modified polyimide composite fibers enhances their interfacial bonding with other materials and their infrared shielding effectiveness. Therefore, by rationally adjusting the ratio of the two, not only can the yarn's excellent mechanical properties be ensured, but its infrared shielding and flame retardant properties can also be significantly improved. In particular, the introduction of the surface-modified polyimide composite fiber enables the yarn to exhibit excellent protection in special environments (such as high temperature or strong radiation environments). Furthermore, the warp yarn density of the yarn in the present invention is 30 to 60 strands / cm, and the weft yarn density is 25 to 50 strands / cm. This weft density design ensures the tightness and stability of the yarn structure while maintaining yarn flexibility. The higher warp and weft yarn density not only enhances the yarn's mechanical strength but also optimizes its infrared shielding and flame retardant properties. This is because the denser weft structure effectively blocks external heat radiation and oxygen infiltration by reducing interfiber gaps, thereby enhancing the yarn's protective properties. In summary, the present invention achieves synergistic improvements in the yarn's mechanical properties, infrared shielding properties, and flame retardant properties by controlling the diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber, designing the mass ratio, and rationally optimizing the yarn weft density. The interaction between the various components enables the yarn of the present invention to have good comprehensive performance, which can meet the use requirements in application scenarios with high strength and high protection requirements.

[0022] The present invention also provides a method for preparing a flame-retardant fabric with infrared shielding performance, comprising the following steps: S1. Preparation of fibers: According to a formula, polyester composite fibers and surface-modified polyimide composite fibers are respectively prepared, wherein the polyester composite fibers are prepared by melt-blending magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol and phthalate and then extruding and spinning the mixture, and the surface-modified polyimide composite fibers are prepared by surface-modifying the polyimide composite fibers with basic zinc carbonate.

[0023] S2. Yarn preparation: The polyester composite fiber prepared in S1 and the surface-modified polyimide composite fiber are blended in a mass ratio, and the blended fibers are spun into yarn using conventional spinning equipment.

[0024] S3. Fabric preparation: The yarns prepared in S2 are used as warp yarns and weft yarns, respectively, and a fabric is prepared by a weaving process according to a weaving density.

[0025] S4. Packaging and Storage: The fabric prepared in S3 is cut, wound, and then packaged. The packaged fabric is stored in a dry, ventilated environment, away from direct sunlight and moisture to ensure stable fabric performance.

[0026] (3) Beneficial technical effects 1. The present invention significantly improves the infrared shielding, flame retardancy and mechanical properties of the fabric through the design of magnesium hydroxide / zinc oxide composite fillers, which has obvious advantages over the existing technology. The synergistic effect of magnesium hydroxide nanowires and zinc oxide particles achieves stronger thermal protection and flame retardancy under high temperature conditions, and the infrared reflection and scattering properties of zinc oxide further enhance the radiation protection ability of the fabric. The nanostructure of magnesium hydroxide improves the dispersibility and tensile strength of the material, while zinc oxide improves the mechanical strength of the composite material through strong interfacial bonding with the matrix. The two show excellent synergy through reasonable component ratio and process optimization, so that the fabric still has excellent comprehensive performance under extreme environments, expanding its application potential in the field of multifunctional protection.

[0027] 2. The present invention significantly improves the comprehensive performance of polyimide composite fibers in terms of flame retardancy, infrared shielding, and thermal management through the synergistic effect of dopamine-surface-modified graphene, polyethylene glycol, and basic zinc carbonate. Compared with the existing technology, dopamine-modified graphene not only improves the dispersibility of graphene, but also enhances the infrared shielding effect and flame retardant properties of the material. Polyethylene glycol, as a dispersant and phase change material, enhances the uniformity and thermal management capabilities of the fiber, ensuring its stable performance in high-temperature environments. Basic zinc carbonate releases flame-retardant gases through thermal decomposition, further enhancing the flame retardant effect of the fiber, and enhances the infrared stealth capability of the material through the infrared reflection effect of the decomposition product zinc oxide. The reasonable ratio of the components and process optimization ensure a synergistic effect, which makes the material show excellent application prospects in the fields of high-temperature protection and thermal stealth.

[0028] 3. The present invention significantly improves the mechanical properties, infrared shielding properties and flame retardant properties of the yarn by precisely controlling the diameter, mass ratio and yarn spinning density of the polyimide composite fiber and the surface-modified polyimide composite fiber. Compared with the existing technology, the innovation of the present invention lies in the introduction of surface-modified fibers, which enhances the flexibility and distribution uniformity of the fibers, while improving the interfacial bonding with the matrix, thereby achieving better overall performance. The yarn exhibits excellent protective effects in high-temperature or strong radiation environments, solving the problem of insufficient mechanical strength and protective performance of traditional fibers in extreme environments. The reasonable ratio of fiber diameter, mass ratio and spinning density ensures the stability and safety of the fiber in high-temperature scenarios, giving it broad application potential in the field of high-intensity protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the SEM scanning electron microscope morphology of the zinc oxide particles prepared in Example 1 of the present invention.

[0030] Figure 2 This is the XRD phase analysis spectrum of the zinc oxide particles prepared in Example 1 of the present invention.

[0031] Figure 3 This is the SEM scanning electron microscope morphology of the sea magnesium hydroxide / zinc oxide composite filler prepared in Example 1 of the present invention.

[0032] Figure 4 This is the XRD phase analysis spectrum of the sea magnesium hydroxide / zinc oxide composite filler prepared in Example 1 of the present invention.

[0033] Figure 5 This is a morphology diagram of the flame-retardant fabric with infrared shielding properties prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0034] To make the objectives, technical solutions and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention.

[0035] In the absence of specific conditions, the operations in the examples are carried out under conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. Parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0036] Table 1 Reagents required for Examples and Comparative Examples and corresponding purchasing companies Example 1

[0037] A flame-retardant fabric with infrared shielding properties, obtained by weaving yarns as warp and weft respectively, wherein the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers; The polyester composite fiber of this embodiment is prepared from the following components in parts by mass: 4.0 parts of magnesium hydroxide / zinc oxide composite filler, 50 parts of polyester chips, 0.5 parts of polyethylene glycol and 0.4 parts of phthalate; The magnesium hydroxide / zinc oxide composite filler of this embodiment is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly supported on the surface of the zinc oxide particles; the surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate; The polyimide composite fiber of this embodiment is prepared from the following components in parts by mass: 0.5 parts of surface-modified graphene, 1.5 parts of polyethylene glycol, 40 parts of 4,4'-diaminodiphenyl ether, 36 parts of pyromellitic dianhydride, and 100 parts of N,N-dimethylformamide; The surface-modified graphene in this embodiment is obtained by surface-modifying graphene oxide with dopamine.

[0038] The preparation method of the magnesium hydroxide / zinc oxide composite filler of this embodiment is as follows: 20 parts of zinc oxide particles, 3.5 parts of magnesium chloride, 1.5 parts of magnesium oxide and 50 parts of deionized water are mixed uniformly by weight and added to a Teflon-lined autoclave, and kept at 150°C for 6 hours. After the reaction is completed, the white precipitate is collected by filtration, and then the white precipitate is washed 3 times with deionized water. Then, the washed white precipitate is added to a stainless steel autoclave with 3.0 parts of sodium hydroxide and 80 parts of anhydrous ethanol, and kept at 110°C for 5 hours. After filtration, the solid powder is collected, then washed 3 times with deionized water, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain a magnesium hydroxide / zinc oxide composite filler. The mass ratio of magnesium hydroxide to zinc oxide is 5:95. The average diameter of the magnesium hydroxide nanowires is 35nm, the average length is 100nm, and the average particle size of the zinc oxide particles is 400nm.

[0039] The polyester composite fiber of this embodiment is prepared as follows: a magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol, and phthalate are uniformly mixed, added to a twin-screw extruder, melt blended, extruded, and ejected through a spinneret. The fibers are cooled to obtain the polyester composite fiber. The twin-screw extruder has a screw aspect ratio of 25:1. The extrusion temperature of the twin-screw extruder is 240°C.

[0040] The preparation method of the surface-modified polyimide composite fiber of this embodiment is as follows: after uniformly mixing 2.5 parts of basic zinc carbonate and 100 parts of 5wt.% sodium hydroxide solution, the polyimide composite fiber is completely immersed in the mixed solution for 30 minutes at a temperature of 60°C. After the immersion is completed, it is washed with deionized water three times and finally dried at room temperature to completely obtain the surface-modified polyimide composite fiber. The preparation method of polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and ultrasonicated for 30 minutes to obtain a uniformly dispersed suspension, then the suspension is added to a reactor, and under a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and pyromellitic dianhydride are added, and the polycondensation reaction is carried out with stirring at 5°C for 10 hours. After the reaction is completed, a polyamic acid mixed solution is obtained, which is allowed to stand and vacuum degassing is performed, and solution spinning is performed to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are subjected to thermal imidization and heat setting stretching treatment at 300°C for 30 minutes, and the polyimide composite fibers are obtained after cooling. The preparation method of surface-modified graphene is as follows: 0.5 parts of graphene oxide are added to 100 parts of deionized water by weight, and after stirring evenly, 0.05 parts of dopamine are added, and then the pH is adjusted to 8.0 with ammonia water. The reaction is continuously stirred at room temperature for 6 hours. After stirring is completed, the mixed solution is centrifuged to collect the solid precipitate, and then the precipitate is washed once with deionized water, and finally dried to constant weight in a vacuum drying oven at room temperature to obtain surface-modified graphene.

[0041] The average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber of this example were 8 μm and 6 μm, respectively. The mass ratio of the polyimide composite fiber to the surface-modified polyimide composite fiber in the yarn was 30:70. The warp yarn had a weaving density of 30 strands / cm, and the weft yarn had a weaving density of 25 strands / cm.

[0042] This embodiment also provides a method for preparing a flame-retardant fabric with infrared shielding properties, comprising the following steps: S1. Preparation of fibers: According to a formula, polyester composite fibers and surface-modified polyimide composite fibers are respectively prepared, wherein the polyester composite fibers are prepared by melt-blending magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol and phthalate and then extruding and spinning the mixture, and the surface-modified polyimide composite fibers are prepared by surface-modifying the polyimide composite fibers with basic zinc carbonate.

[0043] S2. Yarn preparation: The polyester composite fiber prepared in S1 and the surface-modified polyimide composite fiber are blended in a mass ratio, and the blended fibers are spun into yarn using conventional spinning equipment.

[0044] S3. Fabric preparation: The yarns prepared in S2 are used as warp yarns and weft yarns, respectively, and a fabric is prepared by a weaving process according to a weaving density.

[0045] S4. Packaging and Storage: The fabric prepared in S3 is cut, wound, and then packaged. The packaged fabric is stored in a dry, ventilated environment, away from direct sunlight and moisture to ensure stable fabric performance.

[0046] according to Figure 1 As shown, the zinc oxide particles of Example 1 of the present invention are observed by SEM scanning electron microscopy, and the obvious particle morphology can be clearly seen, which further proves the morphology of the zinc oxide particles. Figure 2 The XRD phase analysis spectrum of the zinc oxide particles prepared in Example 1 shows that the obtained zinc oxide has a typical crystalline phase, further confirming the purity and crystal structure of the zinc oxide. Figure 3 The SEM morphology of the magnesium hydroxide / zinc oxide composite filler prepared in Example 1 of the present invention is shown, which proves that the composite filler is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly loaded on the surface thereof, and has a uniform structure and is tightly bonded. Figure 4 The XRD phase analysis spectrum of the composite filler further verifies the phase characteristics of zinc oxide and magnesium hydroxide in the composite filler, indicating that the material composition is clear. Figure 5 This image shows the morphology of the flame-retardant fabric with infrared shielding properties prepared in Example 4 of the present invention. This demonstrates that the flame-retardant fabric, woven with yarns as warp and weft, exhibits excellent infrared shielding and flame-retardant properties, meeting the expected functional requirements. This demonstrates that the present invention has successfully produced a flame-retardant fabric with infrared shielding capabilities through an optimized preparation process, and the morphology and phase of the zinc oxide particles and their composite materials have been effectively verified. Example 2

[0047] A flame-retardant fabric with infrared shielding properties, obtained by weaving yarns as warp and weft respectively, wherein the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers; The polyester composite fiber of this embodiment is prepared from the following components in parts by mass: 6.2 parts of magnesium hydroxide / zinc oxide composite filler, 65 parts of polyester chips, 1.1 parts of polyethylene glycol and 0.7 parts of phthalate; The magnesium hydroxide / zinc oxide composite filler of this embodiment is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly supported on the surface of the zinc oxide particles; the surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate; The polyimide composite fiber of this embodiment is prepared from the following components in parts by mass: 1.4 parts of surface-modified graphene, 2.3 parts of polyethylene glycol, 46.7 parts of 4,4'-diaminodiphenyl ether, 42 parts of pyromellitic dianhydride, and 160 parts of N,N-dimethylformamide; The surface-modified graphene in this embodiment is obtained by surface-modifying graphene oxide with dopamine.

[0048] The preparation method of the magnesium hydroxide / zinc oxide composite filler of this embodiment is as follows: 28 parts of zinc oxide particles, 5.1 parts of magnesium chloride, 2.1 parts of magnesium oxide and 50 parts of deionized water are mixed uniformly by weight and added to a Teflon-lined autoclave, kept warm at 156°C for 7 hours. After the reaction is completed, the white precipitate is collected by filtration, and then the white precipitate is washed three times with deionized water. The washed white precipitate is then added to a stainless steel autoclave with 4.2 parts of sodium hydroxide and 80 parts of anhydrous ethanol, kept warm at 116°C for 7 hours, filtered and collected, and then washed three times with deionized water. Finally, the solid powder is dried in a vacuum drying oven at room temperature to constant weight to obtain the magnesium hydroxide / zinc oxide composite filler. The mass ratio of magnesium hydroxide to zinc oxide is 8:92. The average diameter of the magnesium hydroxide nanowires is 46nm, the average length is 175nm, and the average particle size of the zinc oxide particles is 880nm.

[0049] The polyester composite fiber of this embodiment is prepared as follows: a magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol, and phthalate are uniformly mixed, added to a twin-screw extruder, melt blended, extruded, and ejected through a spinneret. The fibers are cooled to obtain the polyester composite fiber. The twin-screw extruder has a screw length-to-diameter ratio of 31:1. The extrusion temperature of the twin-screw extruder is 252°C.

[0050] The preparation method of the surface-modified polyimide composite fiber of this embodiment is as follows: after uniformly mixing 3.4 parts of basic zinc carbonate and 100 parts of 5 wt.% sodium hydroxide solution, the polyimide composite fiber is completely immersed in the mixed solution for 39 minutes at a temperature of 66°C. After the immersion is completed, it is washed with deionized water three times and finally dried at room temperature to completely obtain the surface-modified polyimide composite fiber. The preparation method of polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and ultrasonicated for 34 minutes to obtain a uniformly dispersed suspension, and then the suspension is added to a reactor, and 4,4'-diaminodiphenyl ether and pyromellitic dianhydride are added under a nitrogen atmosphere, and the polycondensation reaction is carried out with stirring at 11°C for 12 hours. After the reaction is completed, a polyamic acid mixed solution is obtained, and the solution is spun after standing and vacuum degassing to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are thermally imidized and heat-set and stretched at 364°C for 40 minutes, and the polyimide composite fibers are obtained after cooling. The preparation method of surface-modified graphene is as follows: 1.1 parts of graphene oxide are added to 100 parts of deionized water, stirred evenly, and then 0.07 parts of dopamine are added, and then the pH is adjusted to 9.0 with ammonia water. The reaction is continuously stirred at room temperature for 8 hours. After stirring is completed, the mixed solution is centrifuged to collect the solid precipitate, and then the precipitate is washed once with deionized water, and finally dried to constant weight in a vacuum drying oven at room temperature to obtain surface-modified graphene.

[0051] The average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber of this example were 10 μm and 8 μm, respectively. The mass ratio of the polyimide composite fiber to the surface-modified polyimide composite fiber in the yarn was 39:61. The warp yarn weave density of the yarn was 36 strands / cm, and the weft yarn weave density was 32 strands / cm.

[0052] This embodiment also provides a preparation method of a flame-retardant fabric with infrared shielding properties, which is the same as that of Example 1 and will not be repeated here. Example 3

[0053] A flame-retardant fabric with infrared shielding properties, obtained by weaving yarns as warp and weft respectively, wherein the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers; The polyester composite fiber of this embodiment is prepared from the following components in parts by mass: 6.4 parts of magnesium hydroxide / zinc oxide composite filler, 74 parts of polyester chips, 1.6 parts of polyethylene glycol and 1.0 part of phthalate; The magnesium hydroxide / zinc oxide composite filler of this embodiment is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly supported on the surface of the zinc oxide particles; the surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate; The polyimide composite fiber of this embodiment is prepared from the following components in parts by mass: 2.3 parts of surface-modified graphene, 3.1 parts of polyethylene glycol, 50 parts of 4,4'-diaminodiphenyl ether, 45 parts of pyromellitic dianhydride, and 190 parts of N,N-dimethylformamide; The surface-modified graphene in this embodiment is obtained by surface-modifying graphene oxide with dopamine.

[0054] The preparation method of the magnesium hydroxide / zinc oxide composite filler of this embodiment is as follows: 37 parts of zinc oxide particles, 6.2 parts of magnesium chloride, 2.6 parts of magnesium oxide and 50 parts of deionized water are mixed uniformly by weight and added to a Teflon-lined autoclave, kept at 162°C for 8 hours. After the reaction is completed, the white precipitate is collected by filtration, and then the white precipitate is washed three times with deionized water. The washed white precipitate is then added to a stainless steel autoclave with 4.8 parts of sodium hydroxide and 80 parts of anhydrous ethanol, kept at 122°C for 7 hours, filtered and collected, and then washed three times with deionized water. Finally, the solid powder is dried in a vacuum drying oven at room temperature to constant weight to obtain the magnesium hydroxide / zinc oxide composite filler. The mass ratio of magnesium hydroxide to zinc oxide is 11:89. The average diameter of the magnesium hydroxide nanowires is 56nm, the average length is 250nm, and the average particle size of the zinc oxide particles is 1360nm.

[0055] The polyester composite fiber of this embodiment is prepared as follows: a magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol, and phthalate are uniformly mixed, added to a twin-screw extruder, melt blended, extruded, and ejected through a spinneret. The fibers are cooled to obtain the polyester composite fiber. The twin-screw extruder has a screw aspect ratio of 34:1. The extrusion temperature of the twin-screw extruder is 264°C.

[0056] The preparation method of the surface-modified polyimide composite fiber of this embodiment is as follows: after uniformly mixing 4.4 parts of basic zinc carbonate and 100 parts of 5 wt.% sodium hydroxide solution, the polyimide composite fiber is completely immersed in the mixed solution for 48 minutes at a temperature of 74°C. After the immersion is completed, it is washed with deionized water three times and finally dried at room temperature to completely obtain the surface-modified polyimide composite fiber. The preparation method of polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and ultrasonicated for 42 minutes to obtain a uniformly dispersed suspension, and then the suspension is added to a reactor. Under a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and pyromellitic dianhydride are added, and the polycondensation reaction is carried out with stirring at 19°C for 14 hours. After the reaction is completed, a polyamic acid mixed solution is obtained, which is allowed to stand and vacuum degassing is performed, and solution spinning is performed to obtain polyamic acid primary fibers. Then, the polyamic acid primary fibers are thermally imidized and heat-set and stretched at 478°C for 51 minutes, and the polyimide composite fibers are obtained after cooling. The preparation method of surface-modified graphene is as follows: 1.9 parts of graphene oxide are added to 100 parts of deionized water, stirred evenly, and then 0.08 parts of dopamine are added, and then the pH is adjusted to 9.2 with ammonia water. The reaction is continuously stirred at room temperature for 10 hours. After stirring is completed, the mixed solution is centrifuged to collect the solid precipitate, and then the precipitate is washed once with deionized water, and finally dried to constant weight in a vacuum drying oven at room temperature to obtain surface-modified graphene.

[0057] The average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber of this example were 13 μm and 10 μm, respectively. The mass ratio of the polyimide composite fiber to the surface-modified polyimide composite fiber in the yarn was 44:56. The warp yarn weave density of the yarn was 48 strands / cm, and the weft yarn weave density was 43 strands / cm.

[0058] This embodiment also provides a preparation method of a flame-retardant fabric with infrared shielding properties, which is the same as that of Example 1 and will not be repeated here. Example 4

[0059] A flame-retardant fabric with infrared shielding properties, obtained by weaving yarns as warp and weft respectively, wherein the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers; The polyester composite fiber of this embodiment is prepared from the following components in parts by mass: 8.0 parts of magnesium hydroxide / zinc oxide composite filler, 90 parts of polyester chips, 2.5 parts of polyethylene glycol and 1.2 parts of phthalate; The magnesium hydroxide / zinc oxide composite filler of this embodiment is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly supported on the surface of the zinc oxide particles; the surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate; The polyimide composite fiber of this embodiment is prepared from the following components in parts by mass: 3.5 parts of surface-modified graphene, 4.0 parts of polyethylene glycol, 60 parts of 4,4'-diaminodiphenyl ether, 54 parts of pyromellitic dianhydride, and 250 parts of N,N-dimethylformamide; The surface-modified graphene in this embodiment is obtained by surface-modifying graphene oxide with dopamine.

[0060] The preparation method of the magnesium hydroxide / zinc oxide composite filler of this embodiment is as follows: 45 parts of zinc oxide particles, 8.0 parts of magnesium chloride, 3.5 parts of magnesium oxide and 50 parts of deionized water are mixed uniformly by weight and added to a Teflon-lined autoclave, and kept at 170°C for 10 hours. After the reaction is completed, the white precipitate is collected by filtration, and then the white precipitate is washed three times with deionized water. Then, the washed white precipitate is added to 6.0 parts of sodium hydroxide and 80 parts of anhydrous ethanol in a stainless steel autoclave, kept at 130°C for 9 hours, filtered and collected, and then washed three times with deionized water. Finally, the solid powder is dried in a vacuum drying oven at room temperature to constant weight to obtain the magnesium hydroxide / zinc oxide composite filler. The mass ratio of magnesium hydroxide to zinc oxide is 15:85. The average diameter of the magnesium hydroxide nanowires is 70nm, the average length is 350nm, and the average particle size of the zinc oxide particles is 2000nm.

[0061] The polyester composite fiber of this embodiment is prepared as follows: a magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol, and phthalate are uniformly mixed, added to a twin-screw extruder, melt blended, extruded, and ejected through a spinneret. The fibers are cooled to obtain the polyester composite fiber. The twin-screw extruder has a screw length-to-diameter ratio of 40:1. The extrusion temperature of the twin-screw extruder is 280°C.

[0062] The preparation method of the surface-modified polyimide composite fiber of this embodiment is as follows: after uniformly mixing 5.5 parts of basic zinc carbonate and 100 parts of 5 wt.% sodium hydroxide solution by weight, the polyimide composite fiber is completely immersed in the mixed solution for 60 minutes at a temperature of 80°C. After the immersion is completed, it is washed with deionized water three times and finally dried at room temperature to completely obtain the surface-modified polyimide composite fiber. The preparation method of polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and ultrasonicated for 45 minutes to obtain a uniformly dispersed suspension, then the suspension is added to a reactor, and under a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and pyromellitic dianhydride are continued to be added, and the polycondensation reaction is carried out with stirring at 25°C for 15 hours. After the reaction is completed, a polyamic acid mixed solution is obtained, which is allowed to stand and vacuum degassing is performed, and solution spinning is performed to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are thermally imidized and heat-set and stretched at 550°C for 60 minutes, and the polyimide composite fibers are obtained after cooling. The preparation method of surface-modified graphene is as follows: 2.5 parts of graphene oxide are added to 100 parts of deionized water by weight, and after stirring evenly, 0.09 parts of dopamine are added, and then the pH is adjusted to 10.0 with ammonia water. The reaction is continuously stirred at room temperature for 12 hours. After stirring is completed, the mixed solution is centrifuged to collect the solid precipitate, and then the precipitate is washed once with deionized water, and finally dried to constant weight in a vacuum drying oven at room temperature to obtain surface-modified graphene.

[0063] The average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber of this example were 15 μm and 12 μm, respectively. The mass ratio of the polyimide composite fiber to the surface-modified polyimide composite fiber in the yarn was 50:50. The warp yarn had a weft density of 60 yarns / cm, and the weft yarn had a weft density of 50 yarns / cm.

[0064] This embodiment also provides a preparation method of a flame-retardant fabric with infrared shielding properties, which is the same as that of Example 1 and will not be repeated here.

[0065] Comparative Example 1 The method is basically the same as Example 1, except that magnesium hydroxide nanowires are not prepared on the surface of zinc oxide particles, but an equal amount of zinc oxide particles are used to replace the magnesium hydroxide / zinc oxide composite filler.

[0066] Comparative Example 2 The method is basically the same as Example 1, except that magnesium hydroxide powder is used instead of magnesium hydroxide nanowires. The magnesium hydroxide powder is purchased from Jiangsu Zehui Magnesium-based New Material Technology Co., Ltd., and the mass fractions of the added magnesium hydroxide and zinc oxide are the same as the mass fractions of magnesium hydroxide and zinc oxide in the magnesium hydroxide / zinc oxide composite filler.

[0067] Comparative Example 3 The method is basically the same as Example 1, except that the surface of the polyimide composite fiber is not modified by basic zinc carbonate.

[0068] Comparative Example 4 The method is basically the same as Example 1, except that the graphene oxide in the preparation of the polyimide composite fiber is surface-modified with dopamine.

[0069] Comparative Example 5 The method is basically the same as Example 1, except that polyethylene glycol is not added in the preparation of the polyimide composite fiber.

[0070] Performance testing: Mechanical Properties: Mechanical properties were tested using a tensile test. According to the GB / T3923.1-2013 standard, 15 samples measuring 200 mm x 50 mm were taken in both the warp and weft directions and tested at a tensile speed of 100 mm / min. The tensile strength and elongation of the fabric were recorded during the test to evaluate the mechanical properties.

[0071] Flame retardancy: Flame retardancy tests include the Limiting Oxygen Index (LOI) test and the vertical burning test (UL-94). The LOI test is conducted in accordance with GB / T5454-1997. Test specimens are 150 mm x 58 mm in both the warp and weft directions, with 15 samples each. A JF-3 oxygen index analyzer manufactured by Jiangning Analyzer Co., Ltd. in China is used. During the test, fabric samples are placed in an upward-flowing nitrogen and oxygen mixture to determine the minimum oxygen volume percentage required to sustain combustion. Test results are considered valid only if 40%-60% of the samples meet the standard's requirements.

[0072] Infrared shielding performance: The infrared shielding performance of the fabric was tested using a Fluke TislO infrared thermal imager to measure the emissivity of the fabric at 160°C.

[0073] The properties of the fabrics of Examples 1 to 4 and Comparative Examples 1 to 5 are summarized in Table 2.

[0074] Table 2 Summary of the properties of the fabrics of Examples 1 to 4 and Comparative Examples 1 to 5

[0075] The main difference between Comparative Example 1 and Example 1 is that, instead of magnesium hydroxide nanowires, an equal amount of zinc oxide particles was used in place of the magnesium hydroxide / zinc oxide composite filler. As shown in Table 2, the composite filler containing magnesium hydroxide nanowires in Example 1 significantly improves the tensile strength, elongation, and flame retardancy (LOI) of the fabric. This is due to the excellent reinforcing and flame retardant properties of the magnesium hydroxide nanowires, whereas zinc oxide particles alone cannot provide similar reinforcement. Furthermore, the afterflame duration of Example 1 is significantly shortened, demonstrating improved flame retardancy. This is due to the more effective flame retardant mechanism of the magnesium hydroxide nanowires, which decompose at high temperatures to produce water vapor, diluting the combustible gases in the combustion zone and forming a thermal insulation layer. While the zinc oxide particles used in Comparative Example 1 have some flame retardancy, they lack the synergistic effect of the magnesium hydroxide nanowires, resulting in a poorer flame retardant effect. Finally, the relatively low emissivity of Example 1 demonstrates that the addition of magnesium hydroxide nanowires not only enhances the structural properties of the material but also contributes to its infrared shielding properties.

[0076] The main difference between Comparative Example 2 and Example 1 is that magnesium hydroxide powder is used instead of magnesium hydroxide nanowires. As shown in Table 2, the magnesium hydroxide nanowires in Example 1 significantly improve tensile strength and elongation compared to magnesium hydroxide powder. This is because the nanoscale magnesium hydroxide is more evenly distributed within the fiber matrix, forming a better reinforcing network. The larger size of magnesium hydroxide powder makes it difficult to distribute evenly, resulting in a less effective reinforcement than the nanowires. Furthermore, the higher LOI value in Example 1 indicates that magnesium hydroxide nanowires are more effective in flame retardancy than magnesium hydroxide powder. This is because the nanowires have a larger specific surface area and better dispersibility, allowing them to more effectively capture and release moisture during combustion, forming a denser thermal insulation layer. The afterflame duration in Example 1 is also significantly shorter, further demonstrating the more significant flame retardancy of the nanowires. The decreasing emissivity trend indicates that the nanowires also have a positive impact on infrared shielding performance, while the effect of magnesium hydroxide powder is relatively weak.

[0077] The main difference between Comparative Example 3 and Example 1 is that the polyimide composite fiber in Comparative Example 3 has not been surface-modified with basic zinc carbonate. As can be seen from Table 2, the polyimide composite fiber surface-modified with basic zinc carbonate in Example 1 can significantly improve the tensile strength and elongation. This is because the surface modification treatment enhances the interfacial bonding between the fiber and the matrix, thereby improving the overall mechanical properties. In Comparative Example 3, the interfacial bonding between the fiber that has not been surface-modified and the matrix is ​​weak, resulting in a decrease in mechanical properties. In terms of flame retardant properties, the LOI value of Example 1 is higher, indicating that the surface modification treatment is helpful in improving the heat resistance and combustion resistance of the fiber. The presence of basic zinc carbonate may form a protective oxide layer at high temperatures, further improving the flame retardancy. In terms of afterflame time, Example 1 performs better than Comparative Example 3, further illustrating the advantages of surface-modified fibers in flame retardancy, and its effect on emissivity is relatively small.

[0078] The main difference between Comparative Example 4 and Example 1 is that the polyimide composite fiber in Comparative Example 4 utilizes graphene oxide that has not been surface-modified with dopamine. As shown in Table 2, the use of dopamine-surface-modified graphene oxide in Example 1 significantly improves the tensile strength and elongation of the fabric. This is because the dopamine modification enhances the interfacial bonding between the graphene oxide and the polyimide matrix, forming a more uniform fiber structure and thus improving the fiber's mechanical properties. In contrast, the unmodified graphene oxide in Comparative Example 4 exhibits weaker bonding with the matrix, lacking the interfacial synergistic reinforcement effect. In terms of flame retardancy, Example 1 exhibits a higher LOI value. The dopamine-modified graphene oxide forms a more effective protective layer at high temperatures, further enhancing its flame retardancy. The shortened afterflame time also demonstrates that the modified graphene exhibits superior flame retardancy compared to the unmodified graphene. In terms of emissivity, Example 1 significantly outperforms Comparative Example 4. The surface-modified graphene better disperses and reflects infrared radiation, thereby improving infrared shielding performance.

[0079] The main difference between Comparative Example 5 and Example 1 is that no polyethylene glycol was added to Comparative Example 5. As shown in Table 2, the addition of polyethylene glycol to Example 1 significantly improves tensile strength and elongation. This is because polyethylene glycol acts as a plasticizer, improving the flexibility and ductility of the fiber, thereby enhancing mechanical properties. In contrast, in Comparative Example 5, due to the lack of the plasticizing effect of polyethylene glycol, the fiber's flexibility is poor, resulting in a decrease in tensile strength and elongation. In terms of flame retardancy, Example 1 has a higher LOI value, likely because the presence of polyethylene glycol facilitates the formation of a more uniform carbonized layer and phase transition heat absorption during combustion, thereby enhancing the flame retardancy. The shortened afterflame time also indicates that the presence of polyethylene glycol helps improve the flame retardancy of the fiber. However, in terms of emissivity, Example 1 performs better than Comparative Example 5. The presence of polyethylene glycol may improve the dispersion of the surface-modified graphene, thereby enhancing infrared shielding performance.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that any equivalent structural transformations made within the scope of the present invention using the contents of the present invention's description and drawings should be included within the scope of protection of the claims of the present invention.

Claims

1. A flame retardant fabric with infrared shielding performance, characterized in that: The yarns are obtained by weaving as warp yarns and weft yarns respectively, and the yarns are obtained by blending polyester composite fibers and surface-modified polyimide composite fibers; The polyester composite fiber is prepared from the following components in parts by mass: 4.0-8.0 parts of magnesium hydroxide / zinc oxide composite filler, 50-90 parts of polyester chips, 0.5-2.5 parts of polyethylene glycol and 0.4-1.2 parts of phthalate; The magnesium hydroxide / zinc oxide composite filler is composed of zinc oxide particles and magnesium hydroxide nanowires uniformly loaded on the surface of the zinc oxide particles; The surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate; The polyimide composite fiber is prepared from the following components in parts by mass: 0.5-3.5 parts of surface-modified graphene, 1.5-4.0 parts of polyethylene glycol, 40-60 parts of 4,4'-diaminodiphenyl ether, 36-54 parts of pyromellitic dianhydride, and 100-250 parts of N,N-dimethylformamide; The surface-modified graphene is obtained by surface-modifying graphene oxide with dopamine.

2. A flame retardant fabric with infrared shielding performance as claimed in claim 1, characterized in that: The preparation method of the magnesium hydroxide / zinc oxide composite filler is as follows: by weight, 20-45 parts of zinc oxide particles, 3.5-8.0 parts of magnesium chloride, 1.5-3.5 parts of magnesium oxide and 50 parts of deionized water are mixed evenly, and then added into a Teflon-lined high-pressure reactor, and the mixture is kept warm at 150-170°C for 6-10 hours. After the reaction is completed, a white precipitate is collected by filtration, and then the white precipitate is washed with deionized water for 3 times. Subsequently, the washed white precipitate, 3.0-6.0 parts of sodium hydroxide and 80 parts of anhydrous ethanol are added into a stainless steel high-pressure reactor, and the mixture is kept warm at 110-130°C for 5-9 hours. After filtration, solid powder is collected, and then the mixture is washed with deionized water for 3 times. Finally, the mixture is dried in a vacuum drying oven at room temperature to a constant weight to obtain the magnesium hydroxide / zinc oxide composite filler.

3. A flame retardant fabric with infrared shielding properties as claimed in claim 1 or 2, characterized in that: The mass ratio of magnesium hydroxide to zinc oxide is (5-15):(95-85); The average diameter of the magnesium hydroxide nanowires is 35-70 nm, the average length is 100-350 nm, and the average particle size of the zinc oxide particles is 400-2000 nm.

4. The flame-retardant fabric with infrared shielding performance as claimed in claim 1, characterized in that: The preparation method of the polyester composite fiber is as follows: magnesium hydroxide / zinc oxide composite filler, polyester chips, polyethylene glycol and phthalate are mixed evenly, added into a twin-screw extruder, melt blended, then extruded, and fibers are sprayed out through a spinneret, and the polyester composite fiber is obtained after cooling.

5. The flame-retardant fabric with infrared shielding performance as claimed in claim 4, characterized in that: The screw length-to-diameter ratio of the twin-screw extruder is (25-40):1; The extrusion temperature of the twin-screw extruder is 240-280°C.

6. The flame retardant fabric with infrared shielding performance as claimed in claim 1, characterized in that: The preparation method of the surface modified polyimide composite fiber is as follows: after 2.5 to 5.5 parts of basic zinc carbonate and 100 parts of 5wt.% sodium hydroxide solution are mixed evenly by weight, the polyimide composite fiber is completely immersed in the mixed solution, the immersion time is 30 to 60 minutes, the immersion temperature is 60 to 80°C, and after the immersion is completed, it is washed with deionized water for 3 times, and finally dried at room temperature to completely obtain the surface modified polyimide composite fiber.

7. A flame retardant fabric with infrared shielding properties as claimed in claim 1 or 5, characterized in that: The preparation method of the polyimide composite fiber is as follows: surface modified graphene, polyethylene glycol and N,N-dimethylformamide are mixed and then ultrasonicated for 30 to 45 minutes to obtain a uniformly dispersed suspension, then the suspension is added to a reactor, and 4,4'-diaminodiphenyl ether and pyromellitic anhydride are continuously added under a nitrogen atmosphere, and polycondensation is carried out under stirring at 5 to 25°C for 10 to 15 hours, and a polyamic acid mixed solution is obtained after the reaction is completed, and a vacuum degassing treatment is performed after solution spinning to obtain polyamic acid primary fibers, and then the polyamic acid primary fibers are subjected to thermal imidization and heat setting stretching treatment at 300 to 550°C for 30 to 60 minutes, and the polyimide composite fibers are obtained after cooling; The mass ratio of the 4,4'-diaminodiphenyl ether to pyromellitic dianhydride is 1:0.

9.

8. The flame-retardant fabric with infrared shielding performance as claimed in claim 7, characterized in that: The preparation method of the surface modified graphene is as follows: by weight, 0.5-2.5 parts of graphene oxide are added to 100 parts of ionized water, and after stirring evenly, 0.05-0.09 parts of dopamine are added, and then the pH is adjusted to 8.0-10.0 with ammonia water, and the reaction is continuously stirred at room temperature for 6-12 minutes. After the stirring is completed, the mixed solution is centrifuged to collect solid precipitates, and then the precipitates are washed once with deionized water, and finally dried in a vacuum drying oven at room temperature to constant weight to obtain the surface modified graphene.

9. The flame-retardant fabric with infrared shielding performance as claimed in claim 1, characterized in that: The average diameters of the polyimide composite fiber and the surface-modified polyimide composite fiber are 8-15 μm and 6-12 μm respectively; The mass ratio of the polyimide composite fiber to the surface-modified polyimide composite fiber in the yarn is (30-50):(70-50); The warp yarn weaving density of the yarn is 30-60 yarns / cm, and the weft yarn weaving density is 25-50 yarns / cm.

10. A method for preparing a flame-retardant fabric with infrared shielding performance according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preparation of fibers: According to a formula, a polyester composite fiber and a surface-modified polyimide composite fiber are prepared respectively, wherein the polyester composite fiber is prepared by melt-blending a magnesium hydroxide / zinc oxide composite filler, a polyester chip, polyethylene glycol and a phthalate and then extruding and spinning the mixture, and the surface-modified polyimide composite fiber is prepared by surface-modifying the polyimide composite fiber with basic zinc carbonate; S2. Preparation of yarn: The polyester composite fiber and the surface-modified polyimide composite fiber prepared in S1 are blended in a mass ratio, and the blended fiber is spun into yarn using conventional spinning equipment; S3. Fabric preparation: The yarns prepared in S2 are used as warp and weft yarns, respectively, and a fabric is prepared by a weaving process according to the textile density; S4. Packaging and storage: The fabric prepared in S3 is cut, rolled and packaged. The packaged fabric is stored in a dry and ventilated environment, avoiding direct sunlight and moisture to ensure stable fabric performance.

Citation Information

Patent Citations

  • High-heat conductivity halogen-free flame-retardant TPEE elastomer composition

    CN108997718A

  • Graphene polyimide composite fiber and preparation method thereof

    CN113737310A

  • Preparation method of magnesium hydroxide coated zinc oxide composite powder

    CN113929970A

  • Flame-retardant, anti-dripping, antibacterial and warm polyimide flame-retardant polyester blended fabric and preparation method thereof

    CN115386999A

  • Epoxy resin composition

    JP2001335680A

Cited By

  • Anti-ultraviolet textile material and preparation method thereof

    CN119913633A

  • Textile base cloth and production process

    CN120099692A

  • Energy storage device and energy storage system

    CN121484319A

  • Energy storage device and energy storage system

    CN121484319B